The association between adverse childhood experiences and adult cardiac function in the UK Biobank - Quiroz, JC; Cooper, J; McCracken, C; Khanji, MY; Laranjo, L; Aung, N; Lee, AM; Simon, J; Murphy, T; Biasiolli, L; Piechnik, SK; Maurovich-Horvat, P; et al. (Oxford University Press, 2024)
Lay Summary: The importance of early life factors in determining health in later adulthood is increasingly recognized. Numerous studies have shown the links between adverse experiences and trauma in childhood and physical and mental well-being in adulthood. This study explored how adverse childhood experiences (ACEs) might affect heart health later in life. We used the heart images of 30 814 adults in the UK, obtained using cardiac magnetic resonance imaging and their answers to a self-reported questionnaire on traumatic childhood experiences. Our results showed that ACEs of physical abuse, emotional abuse, emotional neglect, and physical neglect were associated with unhealthy cardiac function and structure in adulthood, such as smaller heart chambers, thicker heart walls, and less flexible blood vessels, potentially leading to more serious cardiac problems in the future. These associations persisted even after taking into consideration traditional risk factors, such as obesity, smoking, alcohol intake, exercise level, diabetes, hypertension, high cholesterol, socioeconomic disadvantage, and education level. These findings suggest that dedicated efforts are needed to communicate the impact of ACEs on cardiovascular health to parents, patients, and clinicians and incorporate the discussion of ACEs when assessing cardiovascular risk.